Economic determinants of populism - Carl Leonard Fischer; Lorenz Meister (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
The rise of populism challenges numerous Western democracies and their institutions. In this round-up, we examine economic and societal conditions that are driving forces behind populism. We focus on five domains that are closely interlinked with populist support: globalization, financial crises, migration, inequality, and social mobility. Each domain offers unique insights into how societal shifts, economic disruptions, and perceived injustices can fuel anti-establishment sentiments. As these factors collectively shape the political landscape, understanding their interplay becomes crucial in devising strategies to sustain and strengthen the stability of democracies and institutions.
Keywords: 330; Populismus; Globalisierung; Finanzkrise; Internationale Migration; Einkommensverteilung; Soziale Mobilität; Umverteilung